5w-2=-6(w+4)

Simple and best practice solution for 5w-2=-6(w+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w-2=-6(w+4) equation:


Simplifying
5w + -2 = -6(w + 4)

Reorder the terms:
-2 + 5w = -6(w + 4)

Reorder the terms:
-2 + 5w = -6(4 + w)
-2 + 5w = (4 * -6 + w * -6)
-2 + 5w = (-24 + -6w)

Solving
-2 + 5w = -24 + -6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '6w' to each side of the equation.
-2 + 5w + 6w = -24 + -6w + 6w

Combine like terms: 5w + 6w = 11w
-2 + 11w = -24 + -6w + 6w

Combine like terms: -6w + 6w = 0
-2 + 11w = -24 + 0
-2 + 11w = -24

Add '2' to each side of the equation.
-2 + 2 + 11w = -24 + 2

Combine like terms: -2 + 2 = 0
0 + 11w = -24 + 2
11w = -24 + 2

Combine like terms: -24 + 2 = -22
11w = -22

Divide each side by '11'.
w = -2

Simplifying
w = -2

See similar equations:

| 3x+7=210 | | 14x^2+79x+72=0 | | 7x(15x+24)=6(500-12x) | | 10x+8=-7x+8 | | 7x+23=-23x+293 | | -18x+10=-404 | | 6c^2+11c-10=0 | | -7x+21=-105 | | b^2-5b=6 | | -21x-22=-43 | | b^2-7b+6=0 | | 4(x-7)=12 | | a^2+2a+1=0 | | -2x-4=-30 | | 5x-3=77 | | (a+3)(a-3)=0 | | a^2-9a=0 | | 1x-14=-11.6 | | 14x^3+79x^2+72x=0 | | (4x-1)(5x-2)=0 | | 11-10x=125-31x | | 17x+21=361 | | 3(1-3x)(3+2x)=0 | | 116-6x=30x+16 | | 50-3x=6x+24 | | 9-10x=63-31x | | 3xy+9x+9+3= | | 12-9x=60-30x | | -162-10x=8x+18 | | (2x-1)(3x+4)=0 | | -45-3x=11-10x | | 79-2x=4x+7 |

Equations solver categories